Necesidad de reformar el art. 186 del Código de la niñez y adolescencia, en lo que respecta al seguimiento periódico a los niños, niñas, y adolescentes dados en adopción a personas extranjeras hasta que cumplan su mayoría de edad - Pilca Cabezas, Gonzalo Patricio (2016)
The situation in Ecuador is a society full of problems, one of which is the abandonment of children, and adolescents by their parents, who can be seen daily on the streets of Ecuador able to begging, labor exploitation, sexual, or in the worst victims of white slavery or trafficking in organs, this part of society is very vulnerable, and the Constitution of our country considers as a priority group, but for those who do not enjoy the protection of their biological parents, the State seeks to create fraternal bonds among individuals who for medical reasons can´not father and those who have been abandoned, in a close relationship known as adoption. Adoption has always represented the Ecuador activity easy legal violation, children are handed to wealthy people who knows what purpose, in exchange for a large sum of money, that is why today this activity to meet the established the Organic Code of Children and Adolescents, the Ministry of Economic and Social Inclusion (MIES) changes its structure in order to improve implementation of social policies To this end, the President, Rafael Correa signed Executive Order No. 1356, which provided by institutional restructuring Thus, the Institute for Children and Families (INFA) and the Social Protection Program (PPS) were integrated into the MIES Ecuadorian families initiating adoption proceedings are always looking for relatively young children, which shortens the hopes of having a family who are no longer infants, therefore hopes for these children and adolescents is the adoption by from foreign partners, initiating a process known as international adoption. It is paradoxical, to discover through this research, that foreign partners are more likely to adopt than those who are Ecuadorian, by typical social paradigms and stereotypes, "Everything outside is better than ours" and more regrettable is know that the monitoring that is done living conditions provided by our foreign adoptive children and adolescents is only for a period of two years under Article 186 of the Code on Children and Adolescents, which is insufficient to meet the overall development of an individual. After two years of monitoring by the Ecuadorian State to our countrymen, you get to completely disregard the lives of adopted, therefore this time is inadequate.